Synthesis and Antimicrobial Studies of Cu(II), Ni(II) and Zn(II) Schiff Base Complexes Derived from Substituted 1,2,4-Triazoles and Heteroaromatic Aldehydes - A. Zabin, Sami (Asian Journal of Chemistry, 2011)
The 1,2,4-triazole containing Schiff base metal complexes were prepared by condensation with some heterocyclic aldehydes. The synthesized Schiff bases and their metal complexes were characterized by elemental analysis, UV-visible, FT-IR, 1H NMR and physical measurements. The IR spectra indicate the bidentate behaviour of the ligand towards the divalent metal ions via one azomethine-N and the sulfur atom of the thiol group. The magnetic moments and electronic spectral data suggest a square-planar geometry for Cu(II) and Ni(II) compounds and a tetrahedral geometry for Zn(II) complexes. Elemental analyses data of the metal complexes indicate 2:l molar ratio (ligand:metal) and agree with their proposed structures. The antimicrobial screening results showed that the Schiff bases were bacterial and fungal static agents. The antimicrobial activity was enhanced on coordination with the metal ion. The order of complexes activity was Cu(II) > Ni(II) > Zn(II) complexes. The complexes showed more activity against A. niger fungus than bacterial strains.